Complete Semigroups of Binary Relations Defined by Semilattices of the Class Z−Elementary X−Semilattice of Unions - Diasamidze, Yasha; Makharadze, Shota; Aydın, Ne¸set; Erdo˘gan, Ali (Sarajevo Journal of Mathematics, 2015)
In this paper we investigate idempotents of complete semigroups of binary relations deﬁned by semilattices of the class Z−elementary X−semilattice of unions. For the case where X is a ﬁnite set we derive formulas by calculating the numbers of idempotents of the respective semigroup.